ANALISIS PERMASALAHAN TRANSPARANSI DAN AKUNTABILITAS DALAM PROSES PERENCANAAN ANGGARAN PENDAPATAN DAN BELANJA DESA DI DESA BERBEK - Dewi, Karisma; Nawangsari, Ajeng Tita (Faculty of Economics and Business University of Lampung, 2026)
Budget planning is a financial management process aimed at achieving efficiency in supporting village development while maintaining transparency and accountability. However, several issues affect changes in village budget plans and their implementation. This study aims to identify problems in managing the Village Revenue and Expenditure Budget (APBDes) by considering transparency and accountability in Berbek Village and analyzing how village officials address these problems, particularly in the 2023 planning and 2024 implementation. The study uses a descriptive qualitative approach through interviews, observation, and documentation. Respondents’ opinions were presented as expressed and analyzed to explain the reasons behind their actions. Data analysis was conducted through collection, reduction, presentation, and conclusion stages. The results show that APBDes preparation in Berbek Village meets transparency and accountability principles, as evidenced by APBDes banner documentation and clear accountability reports. Four main problems were found, namely that priority was given to urgent programs when the budget was limited, funding shortfalls were covered by emergency funds recorded in the Revised Budget (PAK), unplanned budget needs were financed from emergency or specific allocation funds, and delays in central government disbursement were addressed with temporary funding from Village Original Income (PADes).